Genital/perigenital inflammatory linear verrucous epidermal nevus: A case series - Debabrata Bandyopadhyay; Abanti Saha (Wolters Kluwer Medknow Publications, 2015)
Background: Inflammatory linear verrucous epidermal nevus (ILVEN) is a distinct variety of keratinocytic epidermal naevus. In contrast to non-inflammatory epidermal naevi, ILVEN are far less common, usually erythematous and intractably pruritic. ILVEN usually appears at birth or early childhood and has a linear distribution following the Blaschko lines. Genital/perigenital involvement is relatively rare. Objectives: To describe the clinical features of 9 children with ILVEN localized to the genital and perigenital areas. Method: A retrospective study of 9 children with ILVEN presenting to a tertiary care Dermatology Clinic between 2007 and 2014 was undertaken. The clinical and histopathological features were reviewed. Results: Nine children (6 females, 3 males) were included in the study based on their characteristic clinicopathological features. The lesions were associated with severe itching in all cases. The mean age at presentation was 4 years (range 1-11 years). Onset of lesions was before 6 months of age in 8 patients. Left sided involvement was twice as common as the right sided one. Male patients had penoscrotal and groin involvement while all the female children had vulvar lesions. None of the children had any extracutaneous abnormalities. The children were treated with topical agents with variable relief or symptoms. Conclusions: The possibility of ILVEN should be considered in every linear genital lesion in children. We have presented the largest series of perigenital ILVEN reported in English literature.